2017
DOI: 10.1002/2017gl073038
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind flow angle and geoeffectiveness of corotating interaction regions: First results

Abstract: A total of 43 Corotating Interaction Region (CIR)‐induced geomagnetic storms during the unusually deep solar minimum of solar cycle 23 (2006–2010) were identified using a superposed epoch analysis technique. Of these 43 events, detailed cross‐spectrum analyses, between the variations in the Z component of the interplanetary magnetic field (IMF Bz) and the equatorial electrojet (EEJ) strength, were performed for 22 events when the daytime EEJ strengths from Jicamarca were available. The analyses revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…It is noticed that the DP2-type electric field fluctuations of ∼60-min periodicity affected equatorial ionosphere on both day (Philippine sector) and night (Peruvian sector) sides. This is consistent with earlier observations of wide range of periodicities 30-40 min (Kikuchi et al, 1996), 25-35 min (Hanumath Sastri et al, 2000, 40 min (Chakrabarty et al, , 2015Rout et al, 2018), ∼30 and ∼60 min (Chakrabarty et al, 2005;Rout et al, 2017) associated with DP2-type electric field perturbations. Another important observation that emerged from present investigation is additional presence of 45-min quasiperiodic DP2type perturbation on night side (Jicamarca sector).…”
Section: Journal Of Geophysical Research: Space Physicssupporting
confidence: 93%
“…It is noticed that the DP2-type electric field fluctuations of ∼60-min periodicity affected equatorial ionosphere on both day (Philippine sector) and night (Peruvian sector) sides. This is consistent with earlier observations of wide range of periodicities 30-40 min (Kikuchi et al, 1996), 25-35 min (Hanumath Sastri et al, 2000, 40 min (Chakrabarty et al, , 2015Rout et al, 2018), ∼30 and ∼60 min (Chakrabarty et al, 2005;Rout et al, 2017) associated with DP2-type electric field perturbations. Another important observation that emerged from present investigation is additional presence of 45-min quasiperiodic DP2type perturbation on night side (Jicamarca sector).…”
Section: Journal Of Geophysical Research: Space Physicssupporting
confidence: 93%
“…A wide range of periodicities of 30–40 min (Kikuchi et al, ), 25–35 min (Hanumath Sastri et al, ), and 40 min (Chakrabarty et al, , ) have been reported by earlier investigations by various measurements. Further, a recent investigation of Rout et al () revealed that periodicities of 30 and 60 min in IMF Bz affected the equatorial ionosphere during the corotating interaction region‐driven geomagnetic storms. However, the penetration of 40‐min periodic fluctuations in IEFy associated with sheath region of an ICME is brought out for the first time by the present investigation.…”
Section: Discussionmentioning
confidence: 98%
“…It is argued that Dst index fails to capture various processes in the magnetosphere‐ionosphere system during geomagnetic storms that include ionospheric Joule heating, outflow, changes in the thermospheric density, particle precipitation, state of the radiation belts, the evolution of the hot‐plasma ions and electrons in the magnetosphere, and also the geomagnetic storm time evolution of the cold plasma of the plasmasphere and plumes. In addition, it is also well known that the CIR‐driven geomagnetic storms can cause significant changes in radiation belt (Tsurutani et al, ) and global ionosphere (Rout et al, ) though the strength of ring current (Dst index) is less. Therefore, it is not surprising that the geoeffectivenss of an ICME event, in which the IMF Bz polarity is northward inside the MC structure and it is fluctuating in the sheath region, may not be captured efficiently by Dst index.…”
Section: Discussionmentioning
confidence: 99%
“…In the E region, Rout et al. (2017) found some results showing that the IMF B z predominantly affect EEJ during HSS events on some occasions, intensifying this current system. However, we did not find any work related to the Es layer responses in equatorial regions during the HSS occurrences.…”
Section: Resultsmentioning
confidence: 99%